Empowering smart customer to participate in electricity supply system - Ahmad Rozelan, Yunus; Fairus , Abu; Juhaini, Jabar; Arfah, Ahmad (Australian Journal of Basic and Applied Sciences, 2015)
In the current discussion towards a more energy efficient supply and demand in household settings, nations such as smart grid, smart meters and smart appliances are of main importance. Malaysia, developing country plan to implement Smart Grid in order to improve their power system in this country at the same time control electricity demand for the next 20 years. The successes of smart grid placement rely on consumers’ acceptance of smart grid products and services. This study use technology acceptance model (TAM) as a model of research in order to test consumer’s acceptance of smart grid technologies. The results suggest that it is important increase the perceived usefulness and ease of use in order to increase intention to use smart grid by customers.